2016
DOI: 10.1007/s00269-016-0828-3
|View full text |Cite
|
Sign up to set email alerts
|

OH defects in quartz in granitic systems doped with spodumene, tourmaline and/or apatite: experimental investigations at 5–20 kbar

Abstract: detectable only in quartz crystals grown from middle and upper crustal sections (such as hydrothermal quartz) and not in quartz from deep roots of orogenic granitoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 23 publications
8
46
0
1
Order By: Relevance
“…Müller et al [26] have already shown that igneous quartz preferentially incorporates H + as a charge-balancing cation in lieu of Li, K and Na. Similar findings have been made more recently for pegmatite quartz [27,28].…”
Section: Trace Element Incorporation Into Quartzsupporting
confidence: 90%
“…Müller et al [26] have already shown that igneous quartz preferentially incorporates H + as a charge-balancing cation in lieu of Li, K and Na. Similar findings have been made more recently for pegmatite quartz [27,28].…”
Section: Trace Element Incorporation Into Quartzsupporting
confidence: 90%
“…Al concentrations in coesite and stishovite are in all cases about two orders of magnitude higher than H concentrations (Fig. 9), as already observed for quartz synthesized from the same starting material (Frigo et al 2016).…”
Section: Mechanism Of Trace Elements Incorporationsupporting
confidence: 60%
“…Similarly to quartz, trace elements may be incorporated by coupled substitutions of Si 4+ by one trivalent (M 3+ ) and one monovalent (M + ) cation Frigo et al 2016). In fact, concentrations of M 3+ (i.e.…”
Section: Mechanism Of Trace Elements Incorporationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many calibrations have been proposed to determine the water content in quartz using IR spectroscopy (Kats 1962;Paterson 1982;Aines et al 1984;Nakashima et al 1995;Libowitzky and Rossman 1997;Stipp et al 2006;Thomas et al 2009), and they have been discussed recently in connection with studies concerning the crystallographic orientations of quartz and the orientations of irradiated polarized IR light (e.g., Stalder and Konzett 2012;Baron et al 2015;Frigo et al 2016). The calibrations of Paterson (1982) and Libowitzky and Rossman (1997) do not require information on the mineral species, and they assume that the absorption coefficients increase linearly with wave number.…”
Section: Differences Among the Ir Calibrationsmentioning
confidence: 99%